Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan - Elsya Azkiyathul Fangiziah; Syahrum Agung; Immas Nurhayati (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This study aims to determine the effect of training and work discipline on the performance of PT. Vallian Lestari Bersama. This study used a quantitative approach with data collection techniques through the distribution of questionnaires or questionnaires. The population in this study is all employees at PT. Vallian Lestari Bersama totaled 50 people, the samples used were 44 people taken using the slovin formula with a precision level of 5%. Data analysis methods used in this study include validity and reliability tests, classical assumption tests, correlation analysis, multiple linear regression analysis, and t and F hypothesis tests processed using the SPSS 25 application. The results showed that there was a strong correlation between training and work discipline on employee performance. The results of the effect of training on employee performance obtained a calculated t value of 6.503 > t table 2.020 with a significant value of 0.000 < 0.05, it can be stated that there is a partial significant influence between training on employee performance, the results of the influence of work discipline on employee performance obtained a calculated t value of 5.550 > ttable 2.020 with a significant value of 0.000 < 0.05, it can be stated that there is a partial significant influence between work discipline on employee performance, the results of the effect of training and work discipline on employee performance obtained a calculated F value of 24.829 > Ftable 3.22 with a significant value of 0.000 < 0.5 so that it can be concluded that there is a simultaneous significant influence between training and work discipline on employee performance of PT. Vallian Lestari Bersama.